The learning hierarchy technique: an instructional analysis tool in engineering education - Alias, Maizam (2005)

(untitled)
Learning hierarchies as the products of learning task analyses have been widely used in the preparation of instructional materials in general. This technique enables the instructor to identify the enabling objectives for a chosen terminal objective in a systematic way. Being systematic increases the chances of identifying all the enabling objectives that are essential to the achievement of the chosen terminal objective. This article describes how the technique was applied to the teaching and learning in engineering, drawing examples from a structural design course in civil engineering. Specifically, the article describes how the learning hierarchy is derived and validated and how it is subsequently used in the design and development of instructional and assessment materials